2016
DOI: 10.1007/s10552-016-0767-9
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inflammatory index and ovarian cancer risk in a large Italian case–control study

Abstract: Background While inflammation has been shown to play an important etiologic role in ovarian carcinogenesis, little is known about the association between inflammatory properties of diet and ovarian cancer risk. Methods We explored the association between the dietary inflammatory index (DII) and ovarian cancer risk in a multicentric Italian case-control study conducted between 1992 and 1999. Cases were 1031 women with incident, histologically confirmed ovarian cancer from 4 areas in Italy. Controls were 2,411… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 46 publications
3
53
1
1
Order By: Relevance
“…In a population of AA women in the United States, a more pro‐inflammatory diet was positively associated with EOC risk. These findings are consistent with the only other study examining the DII and EOC risk . Although few studies have looked specifically at the inflammatory potential of one's diet in relation to ovarian cancer, individual nutrients and dietary patterns that contribute to inflammation have been assessed previously, yet the results have been fairly inconsistent .…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In a population of AA women in the United States, a more pro‐inflammatory diet was positively associated with EOC risk. These findings are consistent with the only other study examining the DII and EOC risk . Although few studies have looked specifically at the inflammatory potential of one's diet in relation to ovarian cancer, individual nutrients and dietary patterns that contribute to inflammation have been assessed previously, yet the results have been fairly inconsistent .…”
Section: Discussionsupporting
confidence: 83%
“…We observed statistically significant effect modification by both menopausal status and age; among post‐menopausal women and women older than 60 years of age, a more pro‐inflammatory diet was strongly associated with an increased risk of EOC, while no association was seen for pre‐menopausal women and women 60 years of age and younger. Studies in breast, endometrial and ovarian cancer observed similar results, where a positive association between the DII and cancer risk was present only among post‐menopausal women, albeit not statistically significant. In these three studies, age was not assessed as a potential effect modifier.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The DII has been associated with risk of various chronic inflammatory conditions such as colorectal cancer (1418) and cardiovascular diseases (19, 20). In Italy, the DII has been shown to be associated with various cancers ranging from those of the digestive tract (15, 21, 22) to hormone-sensitive cancers (2326). …”
Section: Introductionmentioning
confidence: 99%